2004
DOI: 10.1105/tpc.104.024919
|View full text |Cite
|
Sign up to set email alerts
|

The F-Box Protein AhSLF-S2 Controls the Pollen Function of S-RNase–Based Self-Incompatibility

Abstract: Recently, we have provided evidence that the polymorphic self-incompatibility (S) locus-encoded F-box (SLF) protein AhSLF-S 2 plays a role in mediating a selective S-RNase destruction during the self-incompatible response in Antirrhinum hispanicum. To investigate its role further, we first transformed a transformation-competent artificial chromosome clone (TAC26) containing both AhSLF-S 2 and AhS 2 -RNase into a self-incompatible (SI) line of Petunia hybrida. Molecular analyses showed that both genes are corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
168
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(177 citation statements)
references
References 49 publications
5
168
1
Order By: Relevance
“…Analysis of progeny resulting from selfpollination demonstrated that all of the progeny inherited the transgene. Similar results were reported by Qiao et al (2004b) who transferred the Ah-SLF 2 gene of Antirrhinum hispanicum into S 3L S 3L Petunia hybrida. This experiment was conducted with two variations.…”
Section: Competitive Interaction Showed That Slf Was Pollen-ssupporting
confidence: 78%
“…Analysis of progeny resulting from selfpollination demonstrated that all of the progeny inherited the transgene. Similar results were reported by Qiao et al (2004b) who transferred the Ah-SLF 2 gene of Antirrhinum hispanicum into S 3L S 3L Petunia hybrida. This experiment was conducted with two variations.…”
Section: Competitive Interaction Showed That Slf Was Pollen-ssupporting
confidence: 78%
“…Genomic DNA isolation and Southern-blot analysis were performed as described previously (Qiao et al, 2004). DNA (5 mg) was digested, separated on 0.8% agarose gel, and transferred onto Hybond Nt (Amersham) membrane.…”
Section: Southern-blot Analysismentioning
confidence: 99%
“…In vitro binding assays show that PiSLF in Petunia inflata physically interacts with S-RNases, although this interaction is stronger with nonself SRNases than with self S-RNases (Hua and Kao, 2006). Additional protein-protein interaction assays suggest that SLF/SFB may be a component of an SCF (for Skp1-Cullin1-F-box) or SCF-like complex (Qiao et al, 2004;Hua and Kao, 2006). Notably, data from Zhao et al (2010) in Petunia hybrida show that reduction of PhSSK1 (for P. hybrida SLF-interacting Skp-like1) and its Antirrhinum hispanicum ortholog, AhSSK1, is also required for cross-pollen compatibility.…”
mentioning
confidence: 99%